Effects of Berberzs Vulgarzs (L.)Fruit Extract on Antioxidantenzyme Activities, A-Fetoprotein Content and Histology of Hepatocarcinogenic Rats - Motalleb, Gholamreza (2006)
The chemopreventive agent of Berberis vulgaris fruit extract in hepatocarcinogenesis female Sprague Dawley rats was studied to investigate the possible cancer preventive effect of the plant. Total antioxidant activity and phenolic content of BFE extracts were measured. 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical assay was used to determine antioxidant properties of barberry fruit by measuring the decrease in absorbance at 517 nm. In distilled water, BFE showed 82.52&0.64% free radical scavenging activity with an ECS0=0.65. In ethanol, BFE extract showed 73.62+1.88% free radical scavenging activity with an EC=0.658, BHT 67.50&53% (EC=0.612) and Vitamin C 88.56M.43% (EC=0.252), respectively. Meanwhile BFE in 80% methanol had the highest phenolic content (28000+500mg/100g) followed by extract in water (10000+400mg/100g). The Histological evaluation illustrated that there were significant changes in the lesion score of 50 and lOOmgkg/bodyweight BFE in the DABso and DABloo in portal and lobular region compared to DENIAAF control group. However, the liver of DAB2s showed significant changes in the lesion score only in the portal region not in the lobular region. The liver enzymes activity measured were xenobiotic metabolizing enzymes:garnma glutamyl transpeptidase (GGT), and glutathione S-transferase (GST). Alpha feto protein(AFP) level was measured as a liver tumour marker. The results indicated that there were significant differences (p<0.05) in the activities of GGT and GST between DENIAAF rats and normal rats. In liver cancer rats treated with Berberis vulgaris, the activities of GST and GGT were significantly lower w0.05) compared with the DENIAAF group. The findings showed that BFE could reduce the activity of liver enzymes of rats during hepatocarcinogenesis. The results showed that the DENIAAF group had the least increase of body weight compared to other groups. The normal control and normal control treated with BFE had a significantly lower the liver weight to body weight (pc0.05) ratio compared with the DENIAAF group. The DENIAAF groups treated with BFE had a lower liver weight to body weight (p<0.05) ratio compared with the DENIAAF group (except DENIAAF treated with BFE25). The DENIAAF group showed the highest level of AFP (2.014 + 1.013 IUlml). Level of AFP in serum of rats in control, BFE groups (N&, NBS0, NBlO0) and in DEN rats treated with BFE at different doses (DABz5, DABSO and DABloo) were significantly lower (p<0.05) compared with the DENIAAFgroup. DENIAAF control treated with BFE showed significantly decrease in serum AFP concentration (as a tumor marker) compared with DENIAAF control group (p<0.05). Meanwhile, the RT-PCR analysis of hepatocytes illustrated the AFP gene expression in DENIAAF group only.